Color Shade Nets Affect Plant Growth and Seasonal Leaf Quality of Camellia sinensis Grown in Mississippi, the United States - Zhang, Qianwen; Bi, Guihong; Li, Tongyin; Wang, Qiushuang; Xing, Zhiheng; LeCompte, Judson; Harkess, Richard L. (Frontiers in Nutrition, 2022)
Shading modifies the microenvironment and can provide plants with some protection from frequent heat, drought, frost, and hail induced by climate change, and has the potential to improve plant growth, yield, and quality. Tea (Camellia sinensis) is an ancient plant originating from tropical and subtropical regions and prefers to grow in partial shade under the forest canopy. The emerging tea industry in the United States (US) requires research support on establishing tea fields in novel environmental conditions as well as on producing high quality tea products. This study investigated the effects of black, blue, and red shade nets on tea plant growth and seasonal leaf qualities in southeastern US with a humid subtropical climate. When compared to no-shade control, black, blue, and red shade nets increased plant growth index (PGI), net photosynthetic rate (Pn), and stomatal conductance (gs), decreased air and leaf surface temperatures in summer and reduced cold damage in winter. No significant difference was found among the black, blue, and red shade nets on tea plant growth. Varying contents of total polyphenols, carbohydrates, free amino acids, L-theanine, gallic acid, caffeine and catechins in fresh tea leaves were observed among different shade treatments and harvesting seasons. 69.58% of the variations was depicted in a biplot by principal component analysis. Red shade was considered helpful for improving green tea quality by increasing the content of L-theanine and free amino acids in tea leaves collected in spring and fall when compared to no-shade control.